O przywództwie polonijnym w rzeczywistości globalizacji świata - Chodubski, Andrzej (Przegląd Politologiczny, 2018)
This paper indicates that the development or decline in the activity of the Polish diaspora to a large extent depends on how active its leaders are. It shows that the cultural and civilizational reality generates a model of a leader – a participatory individual that solves both his own problems and the problems of his community. In the new civilizational reality, education and professional qualifications are becoming the basic criterion in social stratification and one’s position in the system of socio-political governance. The picture of the Polish diaspora shows that its leaders are usually individuals with strong personalities; psychological features are of primary importance in individuals functioning in public life, including the complexities of life in a diaspora. At present, there are two typical models of leadership in the Polish diaspora. One points to the representatives of the ‘old’ immigration, aiming to cultivate the traditional forms of life among Polish émigrés. The other one represents the latest wave of émigrés, who support the implementation of the values of the global civil society, where national and cultural diversity plays a significant role. In conclusion, it is noted that an important element that generates leadership among Polish émigrés is constituted by traditional political culture, including such mythicized elements as Catholicism, anarchy, democratic ideas and the cult of modernity.